Knowledge Management and Performance: Evidence from Public Universities in Indonesia - A. Adman; S. Suwatno; Disman Disman; Lili Adi Wibowo (Jurnal Ad'ministrare, 2023)
The purpose of this paper is to investigate the impact of knowledge management on performance in public universities. Analyzes data from a sample of 141 respondents using the Partial Least Squares Structural Equation Model (PLS-SEM). The results suggest that knowledge management significantly influence on performance. This study is limited to a specific region in western Indonesia covering 3 universities and specifically focuses on the performance of public universities. Nevertheless, this study provides valuable insights into understanding the determinants of performance particularly in public universities. This study provides new insights into the role of knowledge management in explaining performance in public universities, and highlights the importance of considering the values of knowledge creation, knowledge capture and storage, knowledge sharing, and knowledge application and use, in this context.